New Technologies to Study Functional Genomics of Age-Related Macular Degeneration - Nguyen, Tu; Urrutia-Cabrera, Daniel; Liou, Roxanne Hsiang-Chi; Luu, Chi D.; Guymer, Robyn; Wong, Raymond Ching-Bong (Frontiers in Cell and Developmental Biology, 2021)
Age-related macular degeneration (AMD) is the most common cause of irreversible vision loss in people over the age of 50 in developed countries. Currently, we still lack a comprehensive understanding of the genetic factors contributing to AMD, which is critical to identify effective therapeutic targets to improve treatment outcomes for AMD patients. Here we discuss the latest technologies that can facilitate the identification and functional study of putative genes in AMD pathology. We review improved genomic methods to identify novel AMD genes, advances in single cell transcriptomic to profile gene expression in specific retinal cell types, and summarise recent development of in vitro models for studying AMD using induced pluripotent stem cells, organoids and biomaterial, as well as new molecular technologies using CRISPR/Cas that could facilitate functional studies of AMD-associated genes.